Ø§Ù„ØÙˆØ§Ø± Ø§Ù„ØµÙˆØªÙŠ Ø§Ù„Ù…Ù†ØªØ¬ Ù…Ù† Ù‚Ø¨Ù„ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙƒÙ…Ø¯Ø®Ù„ Ù„ØºÙˆÙŠ ÙÙŠ Ø§ÙƒØªØ³Ø§Ø¨ Ù…Ù‡Ø§Ø±ØªÙŠ Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹ ÙˆØ§Ù„ÙƒÙ„Ø§Ù…: Ø¯Ø±Ø§Ø³Ø© Ù†ÙˆØ¹ÙŠØ© ÙÙŠ Ù…Ø¹Ù‡Ø¯ Ø§Ù„ØªØ¨ÙŠØ§Ù† - Mhd Firdaus Lubis; Sahal Mahfudh; Mohammed Abdulaziz Mohamed Ahmad El Tigani; Hajer Abdullah (UIN ANTASARI, 2026)
This study examines the role of student-produced audio dialogue as linguistic input in the acquisition of listening and speaking skills within the Arabic language environment of Al-Tibyan Islamic Boarding School. Grounded in second language acquisition theory and communicative language teaching, linguistic input is viewed as a meaningful experience shaped by learners’ interaction in authentic contexts. Using a qualitative case study design, data were collected through classroom and dormitory observations, in-depth interviews with students, language supervisors, and program coordinators, as well as document analysis. The findings indicate that student-produced audio dialogues serve as natural, contextual, and comprehensible input that connects formal instruction with daily language practice. Continuous exposure supports auditory habituation, vocabulary retention, pronunciation accuracy, and oral fluency, while encouraging a gradual shift from prepared to spontaneous speech. Delayed and non-intrusive error correction further fosters learner confidence and willingness to communicate. The study concludes that student-produced audio dialogue integratively enhances listening and speaking skills by linking input, interaction, and output within a sustainable institutional language environment.